An analysis of urban public policy regarding science, technology and innovation from the perceptions of stakeholders. A case study for a city of an emerging country (2019)
Rapid advances in science, technology and innovation (STI) have transformed the management of cities, have great potential to improve the requirements of local governments and citizens, and can help generate sustainable urban development and equality, especially in developing countries, to decrease poverty and increase education and health. These topics note the importance of developing STI in urban policies as an integrative element to promote urban development based on the necessities of current and future societies and the importance of knowing the perceptions of different stakeholders in the city with respect to STI